Clinical research advances of isavuconazole in the treatment of invasive fungal diseases - Zhang, Tingting; Shen, Yuyan; Feng, Sizhou (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: Invasive fungal diseases (IFD) are a major global public health concern. The incidence of IFD has increased the demand for antifungal agents. Isavuconazole (ISA) is a new triazole antifungal agent that has shown promising efficacy in the prophylaxis and treatment of invasive fungal diseases. The aim of this review is to summarize the recent real-world experiences of using ISA for the treatment and prevention of IFD. Methods: We performed a comprehensive literature search of the MEDLINE, PubMed, Embase, and Cochrane databases for clinical applications of ISA in the real world. Tables and reference lists are presented for this systematic review. Results: IFD poses a major threat to public health and causes high mortality rates. ISA may provide a good treatment. For example, the efficacy of ISA in the treatment of invasive aspergillosis (IA) is comparable to that of voriconazole, and its efficacy in the treatment of invasive mucormycosis (IM) is similar to that of liposomal amphotericin B (L-AmB); therefore, ISA is recommended as the first-line treatment for IA and IM. ISA can also achieve good efficacy in the treatment of invasive candidiasis (IC) and can be used as an alternative to de-escalation therapy after first-line drug therapy. In addition, most studies have shown the efficacy and safety of ISA for the prophylaxis of IFD. Conclusion: Taken together, ISA are expected to become a new choice for the treatment and prevention of IFD because of their good tolerability, high bioavailability, and few drug interactions.